Ayurvedic formulations: Potential COVID-19 therapeutics? - Anees Ahmed Mahaboob Ali; Andrea Bugarcic; Nenad Naumovski; Reena Ghildyal (Elsevier, 2022)
Background: While Molnupiravir and Paxlovid have recently been approved for use in some countries, there are no widely available treatments for COVID-19, the disease caused by SARS-CoV-2 infection. Herbal extracts have been used to treat respiratory clinical indications by Ayurvedic medicine practitioners with minimal adverse reactions and intense research efforts are currently under way to develop some of these formulations for COVID-19 treatment.Methods: Literature search for in silico, in vitro, in vivo, and clinical studies on the topic of Ayurvedic formulations for potential COVID-19 treatment, in order to present the current state of current knowledge by integrating information across all systems.Results: The search yielded 20 peer reviewed articles on in silico studies examining the interaction of phytoconstituents of popular Ayurvedic formulations with SARS-CoV-2 components and its receptors; five articles on preclinical investigations of the ability of selected Ayurvedic formulations to inhibit functions of SARS-CoV-2 proteins; and 51 completed clinical trials on the efficacy of using Ayurvedic formulations for treatment of mild to moderate COVID-19. Clinical data was available from 17 of the 51 trials. There was a considerable overlap between formulations used in the in silico studies and the clinical trials. This finding was unexpected as there is no clearly stated alignment between studies and the traditional pathway to drug discovery- basic discovery leading to in vitro and in vivo proof of concept, followed by validation in clinical trials. This was further demonstrated in the majority of the in silico studies where focus was on potential antiviral mechanisms, while the clinical trials were focused on patient recovery using oral treatments. In all 17 clinical trials where data was available, Ayurvedic treatments lead to a shorter period to recovery in participants with COVID-19.Conclusion: The most commonly used Ayurvedic treatments for management of respiratory symptoms associated with SARS-CoV-2 infection appear to have prophylactic and/or therapeutic properties. It would be of particular interest to assess synergistic and concomitant systemic effects and antiviral activities of individual phytoconstituents and their combinations in the Ayurvedic treatments.